2015
DOI: 10.1159/000435877
|View full text |Cite
|
Sign up to set email alerts
|

Brief in Person Interventions for Adolescents and Young Adults Following Alcohol-Related Events in Emergency Care: A Systematic Review and European Evidence Synthesis

Abstract: Background: Increasing numbers of youth in need of emergency medical treatment following alcohol intoxication have been a major public health concern in Europe in recent years. Brief interventions (BIs) in the emergency department (ED) could prevent future risky drinking. However, effectiveness and feasibility of this approach are currently unclear. Method: A systematic literature search on controlled trials including participants aged 12-25 years treated in an ED following an alcohol-related event was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 58 publications
2
31
0
4
Order By: Relevance
“…The first review found no significant effects of BI on binge drinking reduction among patients younger than 20 compared to the control groups (Newton et al, 2013). The second review found little to no effect of BI among the 12-25 age group, and that the few preventive effects of BI found, varied considerably regarding the different alcohol outcomes considered (Diestelkamp et al, 2016). These results illustrate the need for high-quality studies in order to draw firmer conclusions on the usefulness of BI in emergency departments.…”
Section: Emergency Departmentsmentioning
confidence: 95%
“…The first review found no significant effects of BI on binge drinking reduction among patients younger than 20 compared to the control groups (Newton et al, 2013). The second review found little to no effect of BI among the 12-25 age group, and that the few preventive effects of BI found, varied considerably regarding the different alcohol outcomes considered (Diestelkamp et al, 2016). These results illustrate the need for high-quality studies in order to draw firmer conclusions on the usefulness of BI in emergency departments.…”
Section: Emergency Departmentsmentioning
confidence: 95%
“…Thus, studies targeting adolescents are important, given the prevalence of high‐risk health‐related behavior such as excessive drinking in this age group . Moreover, existing evidence mainly comes from U. S.–American and Australian trials with unclear implications for high‐volume drinking countries in Europe such as Germany . RCTs involving the important group of intoxicated adolescents are missing even though these patients are regarded as a high‐priority group for preventive health services in Germany and the alcohol‐related PED visit is considered a window for opportunity to reach adolescents for interventions and preventive measures for long‐term problems …”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated for the three primary outcomes: binge‐drinking frequency, number of alcoholic drinks on a typical occasion, and alcohol‐related problems at 3‐month follow‐up. To detect an anticipated effect size of d = 0.26, with a power of 80% and with a type I error of 5% for each of these outcomes, 306 patients (153 patients per group) had to be included, if randomization had occurred at patient level. With an assumed intra‐cluster correlation of 0.05 and an average of 1.264 patients per cluster, we calculated a design effect for cluster randomization of 1.013, which increased the required sample size to 312 patients (156 patients per group).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations